1987
DOI: 10.1017/s0317167100026342
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Subdural Hematoma

Abstract: Abstract:Although relatively uncommon, interhemispheric subdural hematoma (ISDH) occurs more frequently than was suspected before the advent of computerized tomographic (CT) scanning. When its mass is sufficiently large to compress the medial cerebral hemisphere, specific focal neurological abnormalities may occur. These include weakness of the contralateral leg, or contralateral hemiparesis with the leg being weaker than the arm. On the unenhanced CT scan ISDH is seen as a crescent shaped, midline hyperdensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…These clinicians suggest that prompt surgery via a craniotomy is the only way to deal with this condition safely. 8,12,13,16) However, some patients with an ISH have been managed successfully with conservative measures in the acute phase. 2,5,10,14) Although there is no consensus on the ideal management of these hematomas, a flexible treatment plan should be developed.…”
Section: Discussionmentioning
confidence: 99%
“…These clinicians suggest that prompt surgery via a craniotomy is the only way to deal with this condition safely. 8,12,13,16) However, some patients with an ISH have been managed successfully with conservative measures in the acute phase. 2,5,10,14) Although there is no consensus on the ideal management of these hematomas, a flexible treatment plan should be developed.…”
Section: Discussionmentioning
confidence: 99%
“…ISH is usually caused by traumatic laceration of bridging veins between the parieto-occipital cortex and the superior sagittal sinus [1, 2, 5, 9 ± 11,14,17,18, 21, 24]. It has also been described in association with anticoagulant therapy [13,19,20,24,26], shunted hydrocephalus [15], or following aneurysm rupture [8]. In addition, other authors [19,20] found ISH to be a frequent complication in the abused child with whiplash injury of the head.…”
Section: Discussionmentioning
confidence: 99%
“…The most distinctive clinical manifestation of ISH is contralateral leg paresis or hemiparesis with crural predominance known as Falx syndrome [2,3,8,9,11,14,17,20,21,24,26]. Partial motor seizures [11,17,20], signs and symptoms of increased intracranial pressure [15,20], or altered consciousness [5,8,10,13,18] may be prominent features in some patients. Diagnosis is readily made by CT; the finding of a crescent-shaped, hyperdense mass along the interhemispheric fissure with a flat medial margin and a convex lateral border is highly suggestive of ISH [11,17 ± 20, 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, the usual surgical manoeuvre is directed towards removal of the clot. The common surgical procedures are parasagittal craniotomy for evacuation of clot 4,5,11 and the burr hole drainage of haematoma. Glista et al.…”
Section: Discussionmentioning
confidence: 99%